2016
DOI: 10.1155/2016/6104719
|View full text |Cite
|
Sign up to set email alerts
|

Cement Dust Exposure and Perturbations in Some Elements and Lung and Liver Functions of Cement Factory Workers

Abstract: Background. Cement dust inhalation is associated with deleterious health effects. The impact of cement dust exposure on the peak expiratory flow rate (PEFR), liver function, and some serum elements in workers and residents near cement factory were assessed. Methods. Two hundred and ten subjects (50 workers, 60 residents, and 100 controls) aged 18–60 years were studied. PEFR, liver function {aspartate and alanine transaminases (AST and ALT) and total and conjugated bilirubin (TB and CB)}, and serum elements {le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
(20 reference statements)
1
20
3
Order By: Relevance
“…Sameen and Richard et al, reported significant increase in hepatic parameters (AST and ALT) in subjects exposed to cement dust. 9,28 The present study showed no significant change in AST and ALT levels in cement exposed subjects when compared to unexposed subjects.…”
Section: Discussioncontrasting
confidence: 43%
“…Sameen and Richard et al, reported significant increase in hepatic parameters (AST and ALT) in subjects exposed to cement dust. 9,28 The present study showed no significant change in AST and ALT levels in cement exposed subjects when compared to unexposed subjects.…”
Section: Discussioncontrasting
confidence: 43%
“…Similar findings have been reported from other studies [ 26 , 47 ] on the association of ambient air pollution and respiratory ill health and also high levels of particulate matter in residents near industrial plants [ 23 , 25 , 48 ]. Both respiratory symptoms and reduced lung functions have been consistently associated with exposure to PM; duration and frequency of exposure tend to be determining factors [ 36 , 39 , 40 , 49 , 50 ]. Exposure to PM has been repeatedly associated with decreased FEV1 in human studies [ 32 , 42 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Lime is an alkaline material and corrodes biological tissues; silica is a skin abrasive and also damages the lungs; and chromium causes allergic reactions. 7 Many of the studies 3,4,6,8,9,10 done previously demonstrated the effect of cement dust on respiratory system. These studies found out considerable decline in the lung function parameters due to cement dust inhalation.…”
Section: 3mentioning
confidence: 99%